2021
DOI: 10.1182/blood.2021010815
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and prognosis of clonal hematopoiesis in patients with chronic idiopathic neutropenia

Abstract: The incidence and prognosis of clonal hematopoiesis in patients with isolated neutropenia among patients with idiopathic cytopenia of undetermined significance (ICUS), known as ICUS-N or chronic idiopathic neutropenia (CIN) patients, is poorly defined. In the present study we sought to investigate the frequency and clinical significance of mutations of genes implicated in myeloid malignancies using next generation sequencing, in CIN patients (n=185) with a long follow-up. We found that 21/185 patients (11.35%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“… 10 , 21 Recently, the association between CH and anemia as well as neutropenia and monocytosis has been studied. 7 , 22 , 23 In a population-based case–control study, a higher prevalence of CH, particularly with SF3B1 and TP53 mutations, has been observed in older individuals with anemia. The presence of CH did not affect the risk of death in anemic individuals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 10 , 21 Recently, the association between CH and anemia as well as neutropenia and monocytosis has been studied. 7 , 22 , 23 In a population-based case–control study, a higher prevalence of CH, particularly with SF3B1 and TP53 mutations, has been observed in older individuals with anemia. The presence of CH did not affect the risk of death in anemic individuals.…”
Section: Introductionmentioning
confidence: 99%
“… 7 Furthermore, it has been shown that the presence of CH in patients with chronic idiopathic neutropenia did not significantly correlate with the severity of neutropenia but mutations in SRSF2 and IDH1 were associated with malignant transformation. 22 Recently, it was shown in a clinical cohort of cases with primary immune thrombocytopenia (ITP, n = 14) that the presence of CH in ITP patients was closely related to disease severity and treatment responsiveness. Previously, it was described that the presence of mutations in U2AF1 and PPM1D are associated with decreased platelet counts, whereas mutations in DNMT3A , CALR , and JAK2 are associated with increased platelet counts.…”
Section: Introductionmentioning
confidence: 99%
“…36,37,38,39 Among humans and in mice models, certain types of MDS (myelodysplasia)/leukemia preferentially develop in aging females, such as the 5q-syndrome, and in mouse models with haploinsufficiency of cytoskeletal effector mDia1, that recapitulates many features of 5q-syndrome. 40,41 While, clonal hematopoiesis emerges as a still incompletely understood contributor to myelodysplasia in aging humans, 42 a recent study has reported human cases of clonal hematopoiesis harboring hotspots for protein-altering mutations in DNM2. 9 Interestingly, in recent reports, DNM2 (in particular, with loss of function mutation) is associated in a molecular signature with RUNX/RUNXT1 leukemia, 43 and DNM2 was associated with MDS at risk for transformation in the Oncomine database.…”
Section: Discussionmentioning
confidence: 99%
“…conducted an observation study concentrating on the relation between ICUS-N and CH, and found that SRSF2 and IDH1 mutations contributed to a higher risk of myeloid malignancy transformation [15]. However, there was still little data about the mutation status and outcome of ICUS patients [14,20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that CH happened only in a relatively small proportion of ICUS patients with neutropenia (ICUS-N), while it signi cantly increased the risk of malignant transformation [15]. So far, the clinical signi cance and the mutation landscapes of CH in ICUS remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%